MEMBANGUN WEBSITE NATIONAL PARALYMPIC COMMITTEE ( NPC ) INDONESIA DI SURAKARTA SEBAGAI SARANA PUBLIKASI MASYARAKAT - Sipahutar, Revy (Gaung Informatika, 2014)
The website has now become a power in modern times. Website becomes a tool of media information that are easy to execute and understood by the community. NPC is less published information among the general public from background of the problem is the website is designed to facilitate local and inter -local communities see and follow NPC news quickly and easily. One of the problems media information becomes weakness NPC in the field of website that can not be handled by the NPC, the website can impress all NPC employees working conditions. This final project aims to build a website that is used to process and store data information, about data news and activities NPC. This website is expected to provide convenience of visitors in search of information about and also NPC. This website built using HTML, PHP and uses a MySQL database, by using Macromedia Dreamweaver. Testing a website using WebQual method with 30 respondents consisting of four dimensions, (usability, information quality, information quality and overall), website get value of 79,9% acceptable value.